I belong: active learning for children with special needs - Terri Mitchell; Dowling, Jan Levanger (Michigan: High/Scope Educational Research Fundation, 2007)
Contiene: In a perfekt world 1. Disability labels. Components of active learning curriculum for children with special needs. Large-group times. Small-group times. Plan-do-review. Transitions. Adult-child interactions. Engaging with a wide range of behaviors. Integrating curriculum and therapy
Keywords: Educación Especial